Le système du risque à Saint-Martin (Petites Antilles françaises) - Virginie Duvat (Développement Durable et Territoires)
The island of Saint-Martin is an interesting case study for a systemic approach applied to cyclone hazards and the co-evolution of territory and disaster management. The mecanisms which can be observed increase its vulnerability and the progress of hazard management policies is weakened by political and juridical bottlenecks.